The Mental Handicap of a Hostile Environment - Roche, Hannah P. (The Meducator, 2013)
As the Western world continues to progress to new heights of development, the emphasis on the care and rehabilitation of children living with physical and mental disabilities becomes more focused. In schools across the developed world, clubs and societies are formed to promote the incorporation of students with disabilities into our friend groups and ultimately our lives as well. The vast majority of education and social institutes have a zero tolerance policy concerning discrimination against children with mental and physical challenges. Hundreds of charities, companies, and organizations raise funds and awareness in support of this cause. We have an unmistakably beautiful word for these children in our society: special. And that is truly what they are. However, this is not the case for the vast majority of the world’s population. In cultures where ‘different’ is commonly associated with ‘unwanted’, children with mental and physical disabilities are abandoned, neglected, and tossed aside. In Equatorial Guinea, over 77% of the population live in extreme poverty, barely managing to take care of themselves day to day. As a result, children with special needs are disregarded as an extra burden to their families and to their society. How is it that something that comes to define the word special in certain places can be the same thing that makes children undesirable in others? Perhaps the answer lies in the environmental, social and economical factors in which the child is found.